Performance modeling of quartz tube for gravity-driven solid particle solar receiver. (15th June 2023) - Yu, Yupu; Bai, Fengwu; Wang, Zhifeng
Highlights: Particles were heated to a temperature of 156 ∼ 308 ∘ C under an irradiance of 14.9 ∼ 21.7 kW / m 2 Proposing a 3-D transient model with wavelength dependent radiative properties of the quartz and particles integrated. The color-change of quartz tubes leads to a decrease in thermal efficiency only by 4.1% compared with before-color-change case. A double-layer quartz tube design provides the best thermal performance by increasing greenhouse effect to 0.41. Abstract: The interest in high-temperature solar receivers is increasing due to more and more applications in industrial fields. The solid particle is a promising heat transfer fluid for high-temperature receivers owing to the advantages of direct absorption, low cost, and high allowable temperature (∼1300 °C). The re-radiation losses of solid particles inevitably increase with the higher operating temperature. The quartz tube with a spectral selective transmissivity may be used for reducing re-radiation losses. This paper proposed a mathematical model to describe the heat transfer behaviors of the gravity-driven solid particle solar receiver with a quartz tube covered. The wavelength-dependent radiative properties of the quartz tube and particles were approximated by a gray band method. On-sun tests based on a linear-focused solar furnace were conducted, and test results verified the proposed model. Analysis results show that a reduction in β from 3676 m − 1 to 1000 m − 1 can boost the volume absorption effect and increase the solar-to-thermal efficiency from 0.54 to 0.64. A double-layered quartz tube design provides the best thermal performance by increasing the greenhouse effect of the quartz tube from − 0.02 ∼ 0.08 to 0.41 . The analysis results could be used for the optimal design and operation of the gravity-driven solid particle solar receiver.